Shifting Cafe and Culinary Marketing Strategy in West Sumatra Islamic Business Ethics Perspective - Hamda Sulfinadia; Eli Suryani; Jurna Petri Roszi; Elkhairati Elkhairati; Abrian Tanjung (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Purpose: This paper is to find out the shift in the marketing strategy of cafes and culinary delights in West Sumatra from the perspective of Islamic business ethics. Basically the naming of cafes and culinary in this area uses the names of people, names of plants, describes the comfort of a place, and uses Arabic terms. However, since 2018 the naming of cafes and culinary delights has instead used terms that are unusual and tend to be scary, such as Mie Hell, Mie Power Hell, Mie Lightning, Mie Judes Neraka and the like. It turns out that these cafes and culinary delights are in demand by young people, so they are booming. This gives the impression that hell and lightning becomes the menu of food consumed. However, the behavior of traders has been regulated in Islam which is summarized in Islamic business ethics which includes monotheism, justice, balance, responsibility and freedom.Design/Method/Approach: This study uses a qualitative method with a descriptive analysis approach. This method is used to describe the shift in the marketing strategy of cafes and culinary that has a negative nuance in West Sumatra. The data sources come from culinary producers, consumers, and the management of the MUI West Sumatra. Data processing is done by code data, tell data, identify data and generalize data. All data obtained by using triangulation with data sources. The next step is to analyze the naming of cafes and culinary that are not common in West Sumatra by using the theory of Islamic business ethics and the results of the West Sumatra MUI Coordination Meeting, so as to obtain conclusions.Findings: First, the factors that cause West Sumatran cafe and culinary owners to choose unusual names are: 1. Showing product characteristics, spicy flavors are displayed with scary and unusual names; 2. Tight business competition triggers culinary owners to be creative by giving unique and unusual names; 3. Unique and unusual names in cafes and culinary delights make consumers curious, then visit and buy their products. Second, the perception of consumers and the people of West Sumatra on the unusual naming of cafes and culinary delights can be divided into 3, namely agree, disagree, disagree and uncomfortable with the unusual naming of cafes and culinary, and the name must be exchanged with another name that is more Third, a review of Islamic business ethics on naming cafes and culinary delights that choose names that are not common in West Sumatra can be divided into 2 groups: 1) The terms used are clearly contrary to the Shari'ah, namely hell, devil, devil, dajal; 2) Naming cafes and restaurants that use names related to ethical violations such as: Mie Padeh Maut, Mie Baro, Mie Caruik, Bakso Pentol Maut, Mie Pedas Maut, Spicy Sopan'Stek, Mie Padeh Gilo, Mie Pelakor, Mie Padeh Gilo, Mie Judes, Lightning Noodles, and the like. Mie Tapakiek, and the like. Islamic business ethics that are violated are the principles of monotheism, justice, balance in the world and the hereafter and the principle of accountability.Originality/Values: The main research contribution is related to the marketing strategy of cafes and culinary arts using unusual names in West Sumatra.